Antibacterial hemostatic bandage and preparation method thereof

By using modified nano zinc oxide, hydrophobically modified chitosan and vinyl polysiloxane in hemostatic materials, combined with Fe3+ complexing, the excessive blood loss and adhesion of existing hemostatic materials during clot formation is solved, and rapid and firm blood clot formation and reduced infection risk is achieved.

CN119033989BActive Publication Date: 2025-03-04TIANJIN JUNDUN EMERGENCY MEDICAL TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411523897.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-03-04
Estimated Expiration
2044-10-30

AI Technical Summary

Technical Problem

Existing hemostatic materials have the risk of pain, secondary bleeding and infection caused by excessive blood loss and clot adhesion during clot formation.

Method used

Using modified nano zinc oxide, hydrophobic modified chitosan and vinyl polysiloxane, a superhydrophobic layer is formed on the polypropylene nonwoven fabric through spraying and irradiation crosslinking technology, and combined with Fe3+ complexing, the formation and stability of blood clots are promoted.

Benefits of technology

Rapid and firm blood clot formation is achieved, reducing blood loss and peel tension during hemostasis, reducing the risk of infection, and avoiding the risk of free particles entering the blood vessels.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_4
    Figure SMS_4
  • Figure SMS_5
    Figure SMS_5
Patent Text Reader

Abstract

The invention discloses an antibacterial hemostatic bandage and a preparation method thereof, and relates to the technical field of medical supplies. When preparing the antibacterial hemostatic bandage, the present invention first performs surface modification of nano zinc oxide with organosiloxane to obtain modified nano zinc oxide; chitosan is reacted with D, L-lactide to obtain grafted polylactic acid chitosan; grafted polylactic acid chitosan is first reacted with chloroacetyl chloride, and then with oil-based dimethyl tertiary amine to obtain hydrophobically modified chitosan; hydrophobically modified chitosan, modified nano zinc oxide, and vinyl polysiloxane are prepared into a dispersion in dichloromethane, sprayed on a polypropylene non-woven fabric, and immersed in a ferric chloride solution after irradiation cross-linking, and an antibacterial hemostatic bandage is obtained after drying. The antibacterial hemostatic bandage prepared by the present invention has a faster hemostatic speed, good antibacterial property, low blood loss rate, and is easy to remove when replaced due to the surface super-hydrophobicity, reducing secondary injury and secondary bleeding.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of medical supplies, in particular to an antibacterial hemostatic bandage and a preparation method thereof. Background Art

[0002] As a typical medical and sanitary textile, bandages are usually used for first aid and postoperative wound healing. They can create a clean and moist environment for the wound, provide physical support and wound protection, prevent bacterial infection, promote wound healing, reduce the probability of complications and infection, and improve patient comfort. With the development of modern medical technology, various functional bandages have emerged on the premise of meeting basic usage requirements. An ideal function of wound care bandages is to prevent adhesion and make wounds easy to remove.

[0003] Improper wound dressing prolongs wound healing time and creates a high risk of infection. The traditional method of dealing with bleeding is to mechanically press the wound with cotton gauze, which inevitably absorbs blood, causing unnecessary blood loss and gauze adhesion to the wound. The blood absorbed by the gauze forms a solid clot-gauze composite, and forced peeling usually tears the wound, causing secondary bleeding and pain. This causes heavy bleeding before coagulation in processes ranging from common wounds to surgery, as well as in hemophiliacs. To address these problems, active coagulants are used in hemostatic materials to reduce bleeding by accelerating the coagulation process. However, these drugs use free particles, and if they enter the vascular system, they will form microthrombi and affect human health and safety. Despite the progress made in the development of advanced hemostatic materials over the past few decades, there are still two major challenges that need to be addressed: excessive blood loss during clot formation and strong adhesion of clots to hemostatic dressings, leading to pain, secondary bleeding, and possible infection during the removal of wound dressings. Summary of the invention

[0004] The purpose of the present invention is to provide an antibacterial hemostatic bandage and a preparation method thereof to solve the problems existing in the prior art.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0006] The invention discloses an antibacterial hemostatic bandage. The antibacterial hemostatic bandage comprises the following steps: firstly performing surface modification on nano zinc oxide with organic siloxane to obtain modified nano zinc oxide; then reacting chitosan with D,L-lactide to obtain grafted polylactic acid chitosan; firstly reacting the grafted polylactic acid chitosan with chloroacetyl chloride and then with oil-based dimethyl tertiary amine to obtain hydrophobically modified chitosan; and then preparing a dispersion liquid of hydrophobically modified chitosan, modified nano zinc oxide and vinyl polysiloxane in dichloromethane, spraying the dispersion liquid on a polypropylene non-woven fabric, irradiating and cross-linking the dispersion liquid, and then soaking the dispersion liquid in a ferric chloride solution, and drying the dispersion liquid to obtain the antibacterial hemostatic bandage.

[0007] As an optimization, the nano zinc oxide has a particle size of 10-30 nm, a model of DXN-HQ20, and is purchased from Darcin Nanotechnology (Changzhou) Co., Ltd.

[0008] As an optimization, the organosiloxane is allylmethyldimethoxysilane.

[0009] As an optimization, the chitosan has a weight average molecular weight of 90,000 and a deacetylation degree greater than 80%.

[0010] As an optimization, the vinyl polysiloxane model is SYLGARD 184.

[0011] As an optimization, the surface density of the polypropylene nonwoven fabric is 47g / m 2 , purchased from Shanghai Yingzi Nonwoven Fabric Co., Ltd.

[0012] A method for preparing an antibacterial hemostatic bandage comprises the following steps:

[0013] (1) Mix nano zinc oxide and anhydrous ethanol in a mass ratio of 1:(20-30), ultrasonically disperse at room temperature for 20-30 min, add allyl methyl dimethoxy silane (0.4-0.5 times the mass of nano zinc oxide), continue ultrasonically disperse for 5-6 min, reflux at 80-85 ° C and 300-400 r / min for 10-12 h, filter, wash with anhydrous ethanol 4-6 times, and vacuum dry at 60-70 ° C for 6-8 h to obtain modified nano zinc oxide;

[0014] (2) Mix chitosan and toluene in a mass ratio of 1:(20-30), disperse them by ultrasonic at room temperature for 20-30 min, let them stand for swelling for 10-12 h, heat them to 80 °C, add D,L-lactide 5.2-5.4 times the mass of chitosan, stir at 200-300 r / min until dissolved, add stannous octoate 0.15-0.16 times the mass of chitosan, react at 100-110 °C and 200-300 r / min for 28-32 h, stop heating, add methanol / acetic acid solution with a volume ratio of 9:1 0.4-0.45 times the mass of chitosan, react at 150-200 r / min for 1-1.5 h, cool them naturally to room temperature, ultrafilter them using a hollow fiber membrane with a pore size of 1000 Da, wash them with anhydrous ethanol 3-5 times, and vacuum dry them at 60-70 °C for 8-10 h to obtain grafted polylactic acid chitosan;

[0015] (3) Grafted polylactic acid chitosan, chloroacetyl chloride, and N,N-dimethylformamide were mixed uniformly in a mass ratio of 1:(0.09-0.11):(20-30), reacted at 300-400 r / min for 1.5-2 h at room temperature, added 0.24-0.3 times the mass of grafted polylactic acid chitosan with oleyl dimethyl tertiary amine, reacted at 300-400 r / min for 40-42 h at room temperature, ultrafiltered using a hollow fiber membrane with a pore size of 1000 Da, washed with anhydrous ethanol for 4-5 times, and vacuum dried at 60-70 ° C for 8-10 h to obtain hydrophobically modified chitosan;

[0016] (4) Mix the hydrophobically modified chitosan, modified nano zinc oxide, vinyl polysiloxane and dichloromethane in a mass ratio of 1:(0.2-0.3):(2.4-2.8):(24-28), disperse them by ultrasonic at room temperature for 20-30 min, stir at 300-400 r / min for 1-2 h, and heat at 10-12 g / m 2 The antibacterial hemostatic bandage was prepared by spraying the non-woven fabric on a polypropylene substrate, irradiating the fabric at a radiation voltage of 120-130 kV, a radiation current of 1 mA, and a radiation dose of 70-80 KGy, vacuum drying the fabric at 60-70 °C for 6-8 h, blowing the fabric with 430-440 kPa nitrogen at a distance of 15-18 cm for 20-30 min, soaking the fabric in a 20 mmol / L ferric chloride solution at room temperature for 18-20 h, washing the fabric with deionized water for 3-5 times, and vacuum drying the fabric at 60-70 °C for 4-5 h.

[0017] As an optimization, the reaction process of step (2) is as follows:

[0018] .

[0019] As an optimization, the reaction process of step (3) is as follows:

[0020]

[0021] .

[0022] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0023] When preparing the antibacterial hemostatic bandage, the present invention firstly performs surface modification on nano zinc oxide by using allyl methyl dimethoxy silane to obtain modified nano zinc oxide; reacts chitosan with D, L-lactide to obtain grafted polylactic acid chitosan; firstly reacts the grafted polylactic acid chitosan with chloroacetyl chloride and then reacts with oily dimethyl tertiary amine to obtain hydrophobically modified chitosan; and prepares a dispersion liquid of hydrophobically modified chitosan, modified nano zinc oxide and vinyl polysiloxane in dichloromethane, sprays the dispersion liquid on a polypropylene non-woven fabric, crosslinks the dispersion liquid by irradiation, and then immerses the dispersion liquid in a ferric chloride solution, and obtains the antibacterial hemostatic bandage after drying.

[0024] First, the surface of nano zinc oxide is modified with allyl methyl dimethoxy silane to obtain modified nano zinc oxide. The methoxy group on the allyl methyl dimethoxy silane reacts with the hydroxyl group on the surface of the nano zinc oxide, and the allyl methyl dimethoxy silane is grafted on the surface of the nano zinc oxide to improve the compatibility of the nano zinc oxide with subsequent hydrophobically modified chitosan and vinyl polysiloxane, improve the dispersion, prevent agglomeration, and improve the hydrophobicity. The nano zinc oxide also has antibacterial properties, and the double bonds can participate in subsequent cross-linking.

[0025] Secondly, chitosan is reacted with D,L-lactide to obtain grafted polylactic acid chitosan. D,L-lactide undergoes a ring-opening polymerization reaction with the hydroxyl groups on chitosan under the catalysis of stannous octoate, and polylactic acid is grafted on the hydroxyl groups of chitosan. The grafting of polylactic acid improves the hydrophobicity of chitosan, and the oxygen on the polylactic acid chain can participate in the subsequent Fe 3+ The grafted polylactic acid chitosan is first reacted with chloroacetyl chloride and then with oleyl dimethyl tertiary amine to obtain hydrophobically modified chitosan. Chloroacetyl chloride reacts with the amino group on the grafted polylactic acid chitosan to undergo an acylation reaction. The nitrogen and oxygen elements on the amide group generated by the acylation reaction can participate in the subsequent Fe 3+ The remaining chlorine substituent reacts with oily dimethyl tertiary amine to form a quaternary ammonium group. The carbon-carbon double bond on the oily group can participate in the subsequent cross-linking reaction. The quaternary ammonium group with a long carbon chain has excellent antibacterial ability. The grafted long carbon chain quaternary ammonium salt further improves the hydrophobicity of chitosan. The quaternary ammonium group is positively charged and can adhere and aggregate with the negatively charged red blood cell surface substances through the positive charge to quickly form a blood clot. The positive charge can also activate platelets. A large amount of electronegative substances are formed on the surface of the activated platelets, which aggregate with the positively charged quaternary ammonium groups on the hydrophobically modified chitosan under the action of electrostatic attraction, making the blood clot firmer.

[0026] Finally, hydrophobically modified chitosan, modified nano zinc oxide, and vinyl polysiloxane were prepared into a dispersion in dichloromethane, sprayed on a polypropylene non-woven fabric, and then immersed in a ferric chloride solution after irradiation cross-linking. After drying, an antibacterial hemostatic bandage was obtained. Hydrophobically modified chitosan, modified nano zinc oxide, and vinyl polysiloxane formed a super hydrophobic layer on the surface of the polypropylene non-woven fabric. The super hydrophobicity can allow the blood clots on its surface to self-shrink and reduce adhesion to the surface of the antibacterial hemostatic bandage, making the antibacterial hemostatic bandage easy to remove when replaced, and the smaller peeling force avoids blood clots. The cracking of the scab reduces secondary damage and secondary bleeding. At the same time, the double bonds contained in each component undergo free radical polymerization under the action of radiation to form a cross-linked network. The covalent bonds make the hydrophobically modified chitosan, modified nano zinc oxide, and vinyl polysiloxane particles sprayed on the surface of the polypropylene non-woven fabric form a whole, avoiding the risk of free particles entering the blood vessels to form microthrombi. After the cross-linking is completed, it is blown with high-pressure nitrogen to completely remove the free particles, and then immersed in ferric chloride solution. The oxygen and nitrogen elements contained in the hydrophobically modified chitosan and Fe 3+ Complexation, loading Fe on antibacterial hemostatic bandage 3+ , Fe 3+ It can promote platelet aggregation, accelerate the hemostasis process, promote the generation of thrombin, accelerate the coagulation cascade reaction, and promote blood coagulation. 3+ It can also promote the aggregation of red blood cells and form blood clots by binding to hemoglobin, thereby achieving a hemostatic effect. DETAILED DESCRIPTION

[0027] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0028] Example 1

[0029] A method for preparing an antibacterial hemostatic bandage, the method comprising the following steps:

[0030] (1) Mix nano zinc oxide and anhydrous ethanol in a mass ratio of 1:20, disperse them uniformly under ultrasonic conditions at room temperature for 20 min, add allyl methyl dimethoxy silane (0.4 times the mass of nano zinc oxide), continue to disperse them under ultrasonic conditions for 5 min, reflux at 80 °C and 300 r / min for 12 h, filter, wash with anhydrous ethanol for 4 times, and vacuum dry at 60 °C for 8 h to obtain modified nano zinc oxide;

[0031] (2) Chitosan and toluene were mixed in a mass ratio of 1:20, ultrasonically dispersed at room temperature for 20 min, allowed to swell for 12 h, heated to 80 °C, D,L-lactide (5.2 times the mass of chitosan) was added, stirred at 200 r / min until dissolved, stannous octoate (0.15 times the mass of chitosan) was added, reacted at 100 °C, 200 r / min for 32 h, stopped heating, methanol / acetic acid solution (9:1) (0.4 times the mass of chitosan) was added, reacted at 150 r / min for 1.5 h, cooled naturally to room temperature, ultrafiltered using a hollow fiber membrane with a pore size of 1000 Da, washed three times with anhydrous ethanol, and vacuum dried at 60 °C for 10 h to obtain grafted polylactic acid chitosan;

[0032] (3) Grafted polylactic acid chitosan, chloroacetyl chloride, and N,N-dimethylformamide were mixed evenly in a mass ratio of 1:0.09:20, reacted at 300 r / min at room temperature for 1.5 h, added 0.24 times the mass of grafted polylactic acid chitosan with oil-based dimethyl tertiary amine, reacted at 300 r / min at room temperature for 40 h, ultrafiltered using a hollow fiber membrane with a pore size of 1000 Da, washed with anhydrous ethanol 4 times, and vacuum dried at 60 ° C for 8 h to obtain hydrophobically modified chitosan;

[0033] (4) The hydrophobically modified chitosan, modified nano zinc oxide, vinyl polysiloxane and dichloromethane were mixed in a mass ratio of 1:0.2:2.4:24, ultrasonically dispersed at room temperature for 20 min, stirred at 300 r / min for 2 h, and heated to 10 g / m 2 The antibacterial hemostatic bandage was prepared by spraying it on a polypropylene non-woven fabric, irradiating it at a radiation voltage of 120 kV, a radiation current of 1 mA, and a radiation dose of 70 KGy, vacuum drying it at 60 °C for 6 h, blowing it with 430 kPa nitrogen at a distance of 15 cm for 20 min, soaking it in a 20 mmol / L ferric chloride solution at room temperature for 18 h, washing it with deionized water for 3 times, and vacuum drying it at 60 °C for 5 h.

[0034] Example 2

[0035] A method for preparing an antibacterial hemostatic bandage, the method comprising the following steps:

[0036] (1) Mix nano zinc oxide and anhydrous ethanol in a mass ratio of 1:25, disperse under ultrasonic conditions at room temperature for 25 min, add allyl methyl dimethoxy silane (0.45 times the mass of nano zinc oxide), continue to disperse under ultrasonic conditions for 6 min, reflux at 85 °C and 350 r / min for 11 h, filter, wash with anhydrous ethanol for 5 times, and vacuum dry at 65 °C for 7 h to obtain modified nano zinc oxide;

[0037] (2) Chitosan and toluene were mixed in a mass ratio of 1:25, ultrasonically dispersed at room temperature for 25 minutes, allowed to swell for 11 hours, heated to 80°C, D,L-lactide (5.3 times the mass of chitosan) was added, stirred at 250 r / min until dissolved, stannous octoate (0.15 times the mass of chitosan) was added, reacted at 105°C, 250 r / min for 30 hours, stopped heating, methanol / acetic acid solution (9:1) (0.45 times the mass of chitosan) was added, reacted at 200 r / min for 1 hour, cooled naturally to room temperature, ultrafiltered using a hollow fiber membrane with a pore size of 1000 Da, washed 4 times with anhydrous ethanol, and vacuum dried at 65°C for 9 hours to obtain grafted polylactic acid chitosan;

[0038] (3) Grafted polylactic acid chitosan, chloroacetyl chloride, and N,N-dimethylformamide were mixed uniformly in a mass ratio of 1:0.1:25, reacted at 350 r / min at room temperature for 1.5 h, added 0.27 times the mass of grafted polylactic acid chitosan with oil-based dimethyl tertiary amine, reacted at 350 r / min at room temperature for 41 h, ultrafiltered using a hollow fiber membrane with a pore size of 1000 Da, washed with anhydrous ethanol 4 times, and vacuum dried at 65 ° C for 9 h to obtain hydrophobically modified chitosan;

[0039] (4) The hydrophobically modified chitosan, modified nano zinc oxide, vinyl polysiloxane and dichloromethane were mixed in a mass ratio of 1:0.25:2.6:26, ultrasonically dispersed at room temperature for 25 min, stirred at 350 r / min for 1.5 h, and heated to 11 g / m 2 The antibacterial hemostatic bandage was prepared by spraying it on a polypropylene non-woven fabric, irradiating it at a radiation voltage of 125 kV, a radiation current of 1 mA, and a radiation dose of 75 KGy, vacuum drying it at 65 °C for 7 h, blowing it with 435 kPa nitrogen at a distance of 16 cm for 25 min, soaking it in a 20 mmol / L ferric chloride solution at room temperature for 19 h, washing it with deionized water for 4 times, and vacuum drying it at 65 °C for 4 h.

[0040] Example 3

[0041] A method for preparing an antibacterial hemostatic bandage, the method comprising the following steps:

[0042] (1) Mix nano zinc oxide and anhydrous ethanol in a mass ratio of 1:30, disperse them evenly under ultrasonic conditions at room temperature for 30 min, add allyl methyl dimethoxy silane (0.5 times the mass of nano zinc oxide), continue to disperse them under ultrasonic conditions for 6 min, reflux at 85 °C and 400 r / min for 10 h, filter, wash with anhydrous ethanol for 6 times, and vacuum dry at 70 °C for 6 h to obtain modified nano zinc oxide;

[0043] (2) Chitosan and toluene were mixed evenly in a mass ratio of 1:30, ultrasonically dispersed at room temperature for 30 minutes, allowed to swell for 12 hours, heated to 80°C, D,L-lactide (5.4 times the mass of chitosan) was added, stirred at 300 r / min until dissolved, stannous octoate (0.16 times the mass of chitosan) was added, reacted at 110°C, 300 r / min for 32 hours, stopped heating, methanol / acetic acid solution (9:1) (0.45 times the mass of chitosan) was added, reacted at 200 r / min for 1.5 hours, cooled naturally to room temperature, ultrafiltered using a hollow fiber membrane with a pore size of 1000 Da, washed with anhydrous ethanol 5 times, and vacuum dried at 70°C for 10 hours to obtain grafted polylactic acid chitosan;

[0044] (3) Grafted polylactic acid chitosan, chloroacetyl chloride, and N,N-dimethylformamide were mixed evenly in a mass ratio of 1:0.11:30, reacted at 400 r / min for 2 h at room temperature, added 0.3 times the mass of grafted polylactic acid chitosan with oil-based dimethyl tertiary amine, reacted at 400 r / min for 42 h at room temperature, ultrafiltered using a hollow fiber membrane with a pore size of 1000 Da, washed with anhydrous ethanol for 5 times, and vacuum dried at 70 ° C for 10 h to obtain hydrophobically modified chitosan;

[0045] (4) The hydrophobically modified chitosan, modified nano zinc oxide, vinyl polysiloxane and dichloromethane were mixed uniformly in a mass ratio of 1:0.3:2.8:28, ultrasonically dispersed at room temperature for 30 min, stirred at 400 r / min for 1 h, and heated to 12 g / m 2 The antibacterial hemostatic bandage was prepared by spraying it on a polypropylene non-woven fabric, irradiating it at a radiation voltage of 130 kV, a radiation current of 1 mA, and a radiation dose of 80 KGy, vacuum drying it at 70 °C for 6 h, blowing it with 440 kPa nitrogen at a distance of 18 cm for 30 min, soaking it in a 20 mmol / L ferric chloride solution at room temperature for 20 h, washing it with deionized water for 5 times, and vacuum drying it at 70 °C for 4 h.

[0046] Comparative Example 1

[0047] A method for preparing an antibacterial hemostatic bandage, the method comprising the following steps:

[0048] (1) Chitosan and toluene were mixed in a mass ratio of 1:25, ultrasonically dispersed at room temperature for 25 min, allowed to swell for 11 h, heated to 80 °C, D,L-lactide (5.3 times the mass of chitosan) was added, stirred at 250 r / min until dissolved, stannous octoate (0.15 times the mass of chitosan) was added, reacted at 105 °C, 250 r / min for 30 h, stopped heating, methanol / acetic acid solution (9:1) (0.45 times the mass of chitosan) was added, reacted at 200 r / min for 1 h, cooled naturally to room temperature, ultrafiltered using a hollow fiber membrane with a pore size of 1000 Da, washed with anhydrous ethanol 4 times, and vacuum dried at 65 °C for 9 h to obtain grafted polylactic acid chitosan;

[0049] (2) Grafted polylactic acid chitosan, chloroacetyl chloride, and N,N-dimethylformamide were mixed uniformly in a mass ratio of 1:0.1:25, reacted at 350 r / min at room temperature for 1.5 h, added 0.27 times the mass of grafted polylactic acid chitosan with oil-based dimethyl tertiary amine, reacted at 350 r / min at room temperature for 41 h, ultrafiltered using a hollow fiber membrane with a pore size of 1000 Da, washed with anhydrous ethanol 4 times, and vacuum dried at 65 ° C for 9 h to obtain hydrophobically modified chitosan;

[0050] (3) The hydrophobically modified chitosan, vinyl polysiloxane and dichloromethane were mixed in a mass ratio of 1:2.1:21, ultrasonically dispersed at room temperature for 25 min, stirred at 350 r / min for 1.5 h, and heated to 11 g / m 2 The antibacterial hemostatic bandage was prepared by spraying it on a polypropylene non-woven fabric, irradiating it at a radiation voltage of 125 kV, a radiation current of 1 mA, and a radiation dose of 75 KGy, vacuum drying it at 65 °C for 7 h, blowing it with 435 kPa nitrogen at a distance of 16 cm for 25 min, soaking it in a 20 mmol / L ferric chloride solution at room temperature for 19 h, washing it with deionized water for 4 times, and vacuum drying it at 65 °C for 4 h.

[0051] Comparative Example 2

[0052] A method for preparing an antibacterial hemostatic bandage, the method comprising the following steps:

[0053] (1) Mix nano zinc oxide and anhydrous ethanol in a mass ratio of 1:25, disperse under ultrasonic conditions at room temperature for 25 min, add allyl methyl dimethoxy silane (0.45 times the mass of nano zinc oxide), continue to disperse under ultrasonic conditions for 6 min, reflux at 85 °C and 350 r / min for 11 h, filter, wash with anhydrous ethanol for 5 times, and vacuum dry at 65 °C for 7 h to obtain modified nano zinc oxide;

[0054] (2) Chitosan, chloroacetyl chloride and N,N-dimethylformamide were mixed uniformly in a mass ratio of 1:0.23:25, reacted at 350 r / min at room temperature for 1.5 h, added with an amount of oleyl dimethyl tertiary amine equal to the mass of chitosan, reacted at 350 r / min at room temperature for 41 h, ultrafiltered using a hollow fiber membrane with a pore size of 1000 Da, washed with anhydrous ethanol for 4 times, and vacuum dried at 65 °C for 9 h to obtain hydrophobically modified chitosan;

[0055] (3) The hydrophobically modified chitosan, modified nano zinc oxide, vinyl polysiloxane and dichloromethane were mixed evenly in a mass ratio of 1:0.25:2.6:26, ultrasonically dispersed at room temperature for 25 min, stirred at 350 r / min for 1.5 h, and heated to 11 g / m 2 The antibacterial hemostatic bandage was prepared by spraying it on a polypropylene non-woven fabric, irradiating it at a radiation voltage of 125 kV, a radiation current of 1 mA, and a radiation dose of 75 KGy, vacuum drying it at 65 °C for 7 h, blowing it with 435 kPa nitrogen at a distance of 16 cm for 25 min, soaking it in a 20 mmol / L ferric chloride solution at room temperature for 19 h, washing it with deionized water for 4 times, and vacuum drying it at 65 °C for 4 h.

[0056] Comparative Example 3

[0057] A method for preparing an antibacterial hemostatic bandage, the method comprising the following steps:

[0058] (1) Mix nano zinc oxide and anhydrous ethanol in a mass ratio of 1:25, disperse under ultrasonic conditions at room temperature for 25 min, add allyl methyl dimethoxy silane (0.45 times the mass of nano zinc oxide), continue to disperse under ultrasonic conditions for 6 min, reflux at 85 °C and 350 r / min for 11 h, filter, wash with anhydrous ethanol for 5 times, and vacuum dry at 65 °C for 7 h to obtain modified nano zinc oxide;

[0059] (2) Chitosan and toluene were mixed in a mass ratio of 1:25, ultrasonically dispersed at room temperature for 25 minutes, allowed to swell for 11 hours, heated to 80°C, D,L-lactide (5.3 times the mass of chitosan) was added, stirred at 250 r / min until dissolved, stannous octoate (0.15 times the mass of chitosan) was added, reacted at 105°C, 250 r / min for 30 hours, stopped heating, methanol / acetic acid solution (9:1) (0.45 times the mass of chitosan) was added, reacted at 200 r / min for 1 hour, cooled naturally to room temperature, ultrafiltered using a hollow fiber membrane with a pore size of 1000 Da, washed 4 times with anhydrous ethanol, and vacuum dried at 65°C for 9 hours to obtain hydrophobically modified chitosan;

[0060] (3) The hydrophobically modified chitosan, modified nano zinc oxide, vinyl polysiloxane and dichloromethane were mixed evenly in a mass ratio of 1:0.25:2.6:26, ultrasonically dispersed at room temperature for 25 min, stirred at 350 r / min for 1.5 h, and heated to 11 g / m 2 The antibacterial hemostatic bandage was prepared by spraying it on a polypropylene non-woven fabric, irradiating it at a radiation voltage of 125 kV, a radiation current of 1 mA, and a radiation dose of 75 KGy, vacuum drying it at 65 °C for 7 h, blowing it with 435 kPa nitrogen at a distance of 16 cm for 25 min, soaking it in a 20 mmol / L ferric chloride solution at room temperature for 19 h, washing it with deionized water for 4 times, and vacuum drying it at 65 °C for 4 h.

[0061] Comparative Example 4

[0062] A method for preparing an antibacterial hemostatic bandage, the method comprising the following steps:

[0063] (1) Mix nano zinc oxide and anhydrous ethanol in a mass ratio of 1:25, disperse under ultrasonic conditions at room temperature for 25 min, add allyl methyl dimethoxy silane (0.45 times the mass of nano zinc oxide), continue to disperse under ultrasonic conditions for 6 min, reflux at 85 °C and 350 r / min for 11 h, filter, wash with anhydrous ethanol for 5 times, and vacuum dry at 65 °C for 7 h to obtain modified nano zinc oxide;

[0064] (2) Chitosan and toluene were mixed in a mass ratio of 1:25, ultrasonically dispersed at room temperature for 25 minutes, allowed to swell for 11 hours, heated to 80°C, D,L-lactide (5.3 times the mass of chitosan) was added, stirred at 250 r / min until dissolved, stannous octoate (0.15 times the mass of chitosan) was added, reacted at 105°C, 250 r / min for 30 hours, stopped heating, methanol / acetic acid solution (9:1) (0.45 times the mass of chitosan) was added, reacted at 200 r / min for 1 hour, cooled naturally to room temperature, ultrafiltered using a hollow fiber membrane with a pore size of 1000 Da, washed 4 times with anhydrous ethanol, and vacuum dried at 65°C for 9 hours to obtain grafted polylactic acid chitosan;

[0065] (3) Grafted polylactic acid chitosan, chloroacetyl chloride, and N,N-dimethylformamide were mixed uniformly in a mass ratio of 1:0.1:25, reacted at 350 r / min at room temperature for 1.5 h, added 0.27 times the mass of grafted polylactic acid chitosan with oil-based dimethyl tertiary amine, reacted at 350 r / min at room temperature for 41 h, ultrafiltered using a hollow fiber membrane with a pore size of 1000 Da, washed with anhydrous ethanol 4 times, and vacuum dried at 65 ° C for 9 h to obtain hydrophobically modified chitosan;

[0066] (4) The hydrophobically modified chitosan, modified nano zinc oxide, vinyl polysiloxane and dichloromethane were mixed in a mass ratio of 1:0.25:2.6:26, ultrasonically dispersed at room temperature for 25 min, stirred at 350 r / min for 1.5 h, and heated to 11 g / m 2 The antibacterial hemostatic bandage was prepared by spraying the antibacterial bandage on a polypropylene nonwoven fabric, irradiating the antibacterial bandage at a radiation voltage of 125 kV, a radiation current of 1 mA, and a radiation dose of 75 KGy, vacuum drying the antibacterial bandage at 65 °C for 7 h, and blowing the antibacterial bandage at a distance of 16 cm with 435 kPa nitrogen for 25 min.

[0067] In the following test examples, the side of the antibacterial hemostatic bandage sprayed with the superhydrophobic layer is called the front side, and the other side is called the back side.

[0068] The citrated blood used below was anticoagulated rabbit blood purchased from Nanjing Shenghang Biotechnology Co., Ltd.

[0069] The medical gauze used below is Zhende sterile medical gauze piece.

[0070] Test Example 1

[0071] Hemostatic performance test: The hemostatic performance of the prepared antibacterial hemostatic bandage was evaluated by in vitro coagulation time test and bleeding volume test. The specific test method is as follows:

[0072] In vitro coagulation time test: Citrate blood and 0.2 mol / L calcium chloride solution were mixed at a volume ratio of 10:1 to obtain a blood sample. 5 mg of antibacterial hemostatic bandage was placed at the bottom of the test tube, 1 ml of blood sample was added, and the timing was started immediately. The test tube was tilted every 20 seconds to observe the blood flow state. When the initial coagulation state was observed, the timing was stopped immediately and recorded as the coagulation time. The average value was recorded after three times. The control group was not added with antibacterial hemostatic bandage.

[0073] Bleeding volume test: To simulate a wound bandaged with medical gauze, make an 8mm×3mm opening on a silicone tube with an inner diameter of 7.8mm to represent the wound, and cover the opening with a layer of antibacterial hemostatic bandage with medical tape. Use a silicone tube wrapped with 2 layers of ordinary medical gauze as a control. Mix citrate blood with 0.2mol / L calcium chloride solution in a volume ratio of 10:1 to obtain a blood sample. Quickly fill 1.5ml of the blood sample into the silicone tube and place it in a culture dish. Let it stand at room temperature for 10 minutes, remove the test tube from the culture dish, measure the weight increase of the culture dish, record it as the blood loss, and repeat three times to obtain the average blood loss.

[0074] The results are shown in Table 1.

[0075] Table 1

[0076]

[0077] From the comparison of the experimental data of Examples 1 to 3, Comparative Examples 1 to 4 and the control group in Table 1, it can be found that the antibacterial hemostatic bandage prepared by the present invention has a faster coagulation time and a lower blood loss.

[0078] By comparison, the coagulation time of Examples 1 to 3 is shorter than that of Comparative Example 2, indicating that the polylactic acid grafted on the hydrophobically modified chitosan provides Fe 3+ complexation sites to load more Fe 3+ , which increases the coagulation rate.

[0079] By comparison, the coagulation time of Examples 1 to 3 is shorter than that of Comparative Example 3, indicating that the quaternary ammonium salt formed by hydrophobically modified chitosan grafted with oleyl dimethyl tertiary amine provides a good coagulation effect and accelerates blood coagulation.

[0080] By comparison, the coagulation time of Examples 1 to 3 is shorter than that of Comparative Example 4, indicating that the Fe complexed with nitrogen and oxygen on the hydrophobically modified chitosan 3+ It provides a good coagulation effect and greatly improves the coagulation speed.

[0081] By comparison, the coagulation time and average blood loss of Examples 1 to 3 are less than those of the control group, indicating that the antibacterial hemostatic bandage prepared by the present invention can stop bleeding quickly while reducing the amount of blood loss during the hemostasis process, and is friendly to hemophilia patients.

[0082] Test Example 2

[0083] Peeling performance test: Citrate blood and 0.2 mol / L calcium chloride solution were mixed at a volume ratio of 10:1 to obtain a blood sample. 20 μl of blood sample was dripped on the front of the antibacterial hemostatic bandage and cured overnight at 37°C to obtain an antibacterial hemostatic bandage with a blood clot. The back of the antibacterial hemostatic bandage with a blood clot was mounted on a force sensor with a 3M high-strength tape. The force sensor had a capacity of 980 mN and a resolution of 0.1 mN. A thin cotton thread was glued to one side of the blood clot with epoxy resin. The cotton thread was pulled at 0.5 mm / s to peel off the blood clot. The mechanical data F was recorded using an NI USB-6218 multi-function data acquisition device. max , measure the maximum width W of the blood clot, repeat three times and record the average value, calculate and record the blood clot stripping tension F max / W.

[0084] The control group was a 20 μl blood sample dripped onto two stacked normal medical gauze sheets, which were cured overnight at 37°C to obtain medical gauze with blood clots. The medical gauze with blood clots was mounted on the force sensor using 3M high-strength tape, and the top medical gauze was pulled at 0.5 mm / s to peel off the two medical gauze sheets adhered to each other by the blood clots. The mechanical data F was recorded using the NIUSB-6218 multi-function data acquisition device. max , measure the maximum width W of the blood clot, repeat three times and record the average value, calculate and record the blood clot stripping tension F max / W.

[0085] The results are shown in Table 2.

[0086] Table 2

[0087]

[0088] From the comparison of the experimental data of Examples 1 to 3, Comparative Examples 1 to 4 and the control group in Table 2, it can be found that the antibacterial hemostatic bandage prepared by the present invention has a low peeling tension.

[0089] By comparison, the peeling tensions of Examples 1 to 3 are less than that of Comparative Example 1, indicating that the addition of modified nano zinc oxide improves the hydrophobicity of the surface of the antibacterial hemostatic bandage and reduces the peeling tension.

[0090] By comparison, the peeling tension of Examples 1 to 3 is less than that of Comparative Example 2, indicating that the polylactic acid grafted on the hydrophobically modified chitosan provides good hydrophobicity, reduces the wetting of the antibacterial hemostatic bandage by blood, makes the blood clot easier to fall off, and reduces the peeling tension.

[0091] By comparison, the peeling tensions of Examples 1 to 3 are less than that of Comparative Example 3, indicating that the long carbon chain of the quaternary ammonium salt formed by the hydrophobically modified chitosan grafted with oleyl dimethyl tertiary amine has good hydrophobic properties, preventing the blood clot from adhering to the antibacterial hemostatic bandage and reducing the peeling tension.

[0092] By comparison, the peeling tension of Examples 1 to 3 is less than that of the control group, indicating that the antibacterial hemostatic bandage prepared by the present invention can reduce the wetting of the surface by blood, prevent the adhesion of blood clots to the antibacterial hemostatic bandage, reduce the peeling tension, reduce the wound tearing and secondary bleeding caused by the subsequent bandage replacement, and reduce the probability of secondary infection.

[0093] Test Example 3

[0094] Antibacterial performance test: Using the agar plate diffusion method in GB / T 20944.1-2007, the antibacterial hemostatic bandage was cut into a circle with a diameter of 10mm, and the antibacterial performance of the antibacterial hemostatic bandage was evaluated by using Escherichia coli and Staphylococcus aureus. The antibacterial effect of the antibacterial hemostatic bandage was evaluated by measuring the size of its inhibition zone. Using the oscillation method in GB / T 20944.3-2008, the antibacterial hemostatic bandage was cut into 0.75±0.05g samples and mixed with the bacterial solution for 5 minutes, and the oscillated bacterial solution was taken to agar culture medium for culture. The antibacterial rate of the antibacterial hemostatic bandage against Escherichia coli and Staphylococcus aureus was determined by the number of growing colonies, and the data was recorded.

[0095] The results are shown in Table 3.

[0096] Table 3

[0097]

[0098] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 4 in Table 3, it can be found that the antibacterial hemostatic bandage prepared by the present invention has good antibacterial properties.

[0099] By comparison, the diameter of the inhibition zone and the inhibition rate of Examples 1 to 3 are greater than the diameter of the inhibition zone and the inhibition rate of Comparative Example 1, indicating that the addition of modified nano zinc oxide improves the antibacterial property of the antibacterial hemostatic bandage and forms a synergistic antibacterial effect with the quaternary ammonium group on the hydrophobic modified chitosan.

[0100] By comparison, the antibacterial zone diameters and antibacterial rates of Examples 1 to 3 are greater than those of Comparative Example 3, indicating that the quaternary ammonium groups on the hydrophobically modified chitosan have excellent antibacterial properties, and synergistically antibacterial with the modified nano zinc oxide greatly improves the antibacterial properties.

[0101] Test Example 4

[0102] Contact angle test: the prepared antibacterial hemostatic bandage was cut into 1cm×2cm size, flattened with a tabletting mold to make the surface flat and uniform, and the contact angle between the front of the antibacterial hemostatic bandage and water droplets and blood droplets was tested with a water contact angle tester. The test method was to drop 5μL of pure water or citrate blood onto the front of the antibacterial hemostatic bandage at standard atmospheric pressure and 20°C, measure the contact angle after the droplet stayed for 5s, and record the data.

[0103] The results are shown in Table 4.

[0104] Table 4

[0105]

[0106] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 4 in Table 4, it can be found that the front side of the antibacterial hemostatic bandage prepared by the present invention has superhydrophobicity.

[0107] By comparison, the water drop contact angle and the blood drop contact angle of Examples 1 to 3 are greater than those of Comparative Example 1, indicating that the surface of nano zinc oxide is hydrophobic after being modified with organosiloxane, thereby improving the hydrophobicity of the front side of the antibacterial hemostatic bandage.

[0108] By comparison, the water drop contact angle and the blood drop contact angle of Examples 1 to 3 are greater than those of Comparative Example 2, indicating that the polylactic acid grafted on the hydrophobically modified chitosan has excellent hydrophobic effect, and good hydrophobic effect brings about low peeling tension.

[0109] By comparison, the water drop contact angle and the blood drop contact angle of Examples 1 to 3 are greater than those of Comparative Example 3, indicating that the long carbon chain quaternary ammonium group on the hydrophobically modified chitosan also has a good hydrophobic effect, making the surface of the antibacterial hemostatic bandage show superhydrophobicity.

[0110] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.

Claims

1. An antibacterial hemostatic bandage, characterized in that: The antibacterial hemostatic bandage comprises the following steps: firstly modifying the surface of nano zinc oxide with organosiloxane to obtain modified nano zinc oxide; reacting chitosan with D,L-lactide to obtain grafted polylactic acid chitosan; firstly reacting the grafted polylactic acid chitosan with chloroacetyl chloride and then with oily dimethyl tertiary amine to obtain hydrophobically modified chitosan; preparing a dispersion of hydrophobically modified chitosan, modified nano zinc oxide and vinyl polysiloxane in dichloromethane, spraying the dispersion on a polypropylene non-woven fabric, crosslinking the dispersion by irradiation, and then soaking the dispersion in a ferric chloride solution, and drying the dispersion to obtain the antibacterial hemostatic bandage; The organosiloxane is allylmethyldimethoxysilane.

2. The antibacterial hemostatic bandage according to claim 1, characterized in that: The particle size of the nano zinc oxide is 10-30 nm, and the model is DXN-HQ20.

3. The antibacterial hemostatic bandage according to claim 1, characterized in that: The weight average molecular weight of the chitosan is 90,000, and the degree of deacetylation is greater than 80%.

4. The antibacterial hemostatic bandage according to claim 1, characterized in that: The vinyl polysiloxane model is SYLGARD 184.

5. A method for preparing an antibacterial hemostatic bandage, characterized in that: The method comprises the following preparation steps: (1) Mix nano zinc oxide and anhydrous ethanol in a mass ratio of 1:(20-30), ultrasonically disperse at room temperature for 20-30 min, add allyl methyl dimethoxy silane (0.4-0.5 times the mass of nano zinc oxide), continue ultrasonically disperse for 5-6 min, reflux at 80-85 ° C and 300-400 r / min for 10-12 h, filter, wash with anhydrous ethanol 4-6 times, and vacuum dry at 60-70 ° C for 6-8 h to obtain modified nano zinc oxide; (2) Mix chitosan and toluene in a mass ratio of 1:(20-30), disperse them by ultrasonic at room temperature for 20-30 min, let them stand for swelling for 10-12 h, heat them to 80 °C, add D,L-lactide 5.2-5.4 times the mass of chitosan, stir at 200-300 r / min until dissolved, add stannous octoate 0.15-0.16 times the mass of chitosan, react at 100-110 °C and 200-300 r / min for 28-32 h, stop heating, add methanol / acetic acid solution with a volume ratio of 9:1 0.4-0.45 times the mass of chitosan, react at 150-200 r / min for 1-1.5 h, cool them naturally to room temperature, ultrafilter them using a hollow fiber membrane with a pore size of 1000 Da, wash them with anhydrous ethanol 3-5 times, and vacuum dry them at 60-70 °C for 8-10 h to obtain grafted polylactic acid chitosan; (3) Grafted polylactic acid chitosan, chloroacetyl chloride, and N,N-dimethylformamide were mixed uniformly in a mass ratio of 1:(0.09-0.11):(20-30), reacted at 300-400 r / min for 1.5-2 h at room temperature, added 0.24-0.3 times the mass of grafted polylactic acid chitosan with oleyl dimethyl tertiary amine, reacted at 300-400 r / min for 40-42 h at room temperature, ultrafiltered using a hollow fiber membrane with a pore size of 1000 Da, washed with anhydrous ethanol for 4-5 times, and vacuum dried at 60-70 ° C for 8-10 h to obtain hydrophobically modified chitosan; (4) Mix the hydrophobically modified chitosan, modified nano zinc oxide, vinyl polysiloxane and dichloromethane in a mass ratio of 1:(0.2-0.3):(2.4-2.8):(24-28), disperse them by ultrasonic at room temperature for 20-30 min, stir at 300-400 r / min for 1-2 h, and heat at 10-12 g / m 2 The antibacterial hemostatic bandage was prepared by spraying the non-woven fabric on a polypropylene substrate, irradiating the fabric at a radiation voltage of 120-130 kV, a radiation current of 1 mA, and a radiation dose of 70-80 KGy, vacuum drying the fabric at 60-70 °C for 6-8 h, blowing the fabric with 430-440 kPa nitrogen at a distance of 15-18 cm for 20-30 min, soaking the fabric in a 20 mmol / L ferric chloride solution at room temperature for 18-20 h, washing the fabric with deionized water for 3-5 times, and vacuum drying the fabric at 60-70 °C for 4-5 h.

6. The method for preparing an antibacterial hemostatic bandage according to claim 5, characterized in that: The reaction process of grafting polylactic acid chitosan in step (2) is as follows: 。 7. The method for preparing an antibacterial hemostatic bandage according to claim 5, characterized in that: The reaction process of the hydrophobically modified chitosan in step (3) is as follows: 。

Citation Information

Patent Citations

  • Antibacterial nano cuprous oxide / chitosan grafted polyacrylate emulsion as well as preparation method and application thereof

    CN112724342A

  • Preparation method of chitin medical dressing for rapid hemostasis

    CN113995882A